SERANGGA-SERANGGA YANG BERASOSIASI PADA TANAMAN TOMAT (Lycopersicum esculentum Mill.) DI KELURAHAN KAMASI KOTA TOMOHON - Brigita H. Pondaag; Robert W. Tairas; Daisy Kandowangko (COCOS, 2022)
ABSTRACTInsects associated with tomato plants are both pests and beneficial insects such as predators,parasitoids, and some are useful as flower pollinators and destroyers of organic matter. The level ofstability of an agricultural ecosystem is determined by the structure of the trophic network and theinteractions between community components including herbivores (pests), carnivores, namelypredators and parasites. This study aims to inventory the insects associated with tomato plants inKamasi Village, Tomohon City. This research was conducted using two traps, namely the Pitfall Trap,the Yellow Sticky Trap which was installed every three days in one month of observation, and directcapture using the Insect Net. Pitfall traps are placed at 10 different points (using the zig-zag method)in 1 planting area. While the Yellow sticky trap is placed at 3 points of the planting area, namely theleft, right and center, the insects caught are labeled. Then it was taken to the laboratory of theDepartment of Pests and Plant Diseases, University of Sam Ratulangi Manado to be observed. Theresults of the study found that the insects associated with tomato plants in Kamasi Village, TomohonCity for Insect Nets were found to have a total of 13 types of insects, namely the Order Orthoptera,Family Acrididae, Order Coleoptera, Family Scarabaeidae, Staphylinidae, Chrysomelidae,Coccinellidae and Chantaridae, Order Diptera, Family Syrphidae. , Dolichopodidae and Asilidae,Order Hymenoptera Family Halictidae, Order Hemiptera Families Alydidae and Miridae, OrderLepidoptera Family Noctuidae. The Pitfall Trap was found to have 12 types of insects, namely theOrder Orthoptera, Family Gryllidae, Order Coleoptera, Family Scarabaeidae, Staphylinidae,Scolytidae and Ptinidae, Order Dermaptera, Family Forficulidae, Order Diptera, Family Drosophilidae,Order Hymenoptera, Family Formicidae, Order Hemiptera, Familiaridae, Colillomidae. Isotomidae andSminthuridae. The Yellow Sticky Trap was found to have 1 type of insect, namely the Order Diptera,Family Tephritidae. From the results of the study, it can be concluded that the insects associated withthe Tomato plant are 8 Orders, 24 Families consisting of insect pests, 11 Families from 5 Orders,insects as natural enemies (predators) 9 Families from 4 Orders, pollinator insects 1 Family from 1Order and decomposer insects of 3 Families of 1 Order.Keyword : insect, Association, tomatoes, garden